2017
DOI: 10.5937/ekonhor1703193t
|View full text |Cite
|
Sign up to set email alerts
|

Model for the supply chain management based on the interval type-2 fuzzy numbers and the TOPSIS method

Abstract: The Performance improvement that leads to an increase in business efficiency, both for the enterprises integrated in the supply chain and the entire supply chain, represents one of the basic strategic management problems. A solution to this problem, among other things, can be obtained by measuring and improving the performance of the supply chain, which simultaneously represents the basic purpose of this research study. The relative importance of performances and the values of their key performance indices are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Interval type-2 fuzzy sets present a special case of generalized type-2 fuzzy sets, so that the computational effort with the interval type-2 fuzzy sets is reduced (Chen and Lee, 2010). Some researchers suggested the application of interval type-2 fuzzy sets for modelling of different uncertainties (Chen and Wang, 2013; Kahraman et al, 2014; Tadić and Đorđević, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interval type-2 fuzzy sets present a special case of generalized type-2 fuzzy sets, so that the computational effort with the interval type-2 fuzzy sets is reduced (Chen and Lee, 2010). Some researchers suggested the application of interval type-2 fuzzy sets for modelling of different uncertainties (Chen and Wang, 2013; Kahraman et al, 2014; Tadić and Đorđević, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that type-2 fuzzy sets are more suitable to represent uncertainties than type-1 fuzzy sets. These fuzzy numbers are widely used to solve different decision-making problems [14,15,16]. The solution of the considered problem can be given by using the many multi-criteria optimization methods.…”
Section: Introductionmentioning
confidence: 99%